APPLICATION OF OVERALL EQUIPMENT EFFECTIVENESS (OEE) TO MEASURE THE EFFECTIVENESS OF EQUIPMENT DISSOLUTION TESTER AT DEXA DEVELOPMENT CENTER (International Journal of Psychosocial Rehabilitation, 2020)
Productivity encourages fast and precise sample work according to the target. To know a job is graded productive or not seen from how a job can be absorbed in accordance with the target. Similarly, with the tool dissolution tester, when a dissolution tester works then the main thing that becomes a reference is how the tool works and can be absorbed in accordance with the target. Calculation with Overall Equipment Effectiveness (OEE) can be a reference to how dissolution tester can absorb the work especially dissolution work in Dexa Development Center. OEE can measure the effectiveness with the continuous production system measured using where further identification with six big losses and advanced analysis using the Fishbone diagram, so that the later will be found troubleshooting recommendations. The value of OEE in the period of 2019 is 64.98% The result of the identification of six big losses and fishbone diagrams in the period of 2019 obtained a significant losses is a breakdown process of 47.4%. Based on the result of OEE and identification cause by using Six Big Losses, company should maintain not only the machine which is Dissolution tester but also knowledge of workers that the operator of Dissolution Tester itself.